The biogeographical influence of the Tankwa Karoo Basin on reptile distribution in south-western South Africa - Meyer, A.; Mouton, P.L.F.; Mucina, Ladislav (Taylor & Francis Group, 2010)
Point distribution data were used to evaluate the biogeographical influence of the arid Tankwa Karoo Basin on the distribution of reptiles in the south-western districts of South Africa. Under-representation of the Tankwa Karoo in the dataset required an additional field survey of this region. Prior to the survey, available records from the Tankwa Karoo Basin represented only 13 reptile species. A total of 36 species (24 lizards, nine snakes, three chelonians) was recorded during our survey of this area. Turnover across the Basin is high, species richness is lower than in surrounding mountainous areas and there are no species endemic to the area. The Tankwa Karoo Basin acts as a dispersal barrier for many reptile species occurring in the surrounding more mesic areas. At the same time, the ranges of a number of typical northern, arid-adapted species extend southward along the Tankwa plains. A number of species range extensions in the region are reported.